Religious Moderation in the Qur'an: A Comparative Study of Tafsir Ath-Thabari and Tafsir al-Maraghi - Nur Ulfatul Jannah; Kiki Muhammad Hakiki; Beko Hendro (Jurnal Semiotika Quran, 2025)
This study examines the concept of religious moderation in the Qur’an by employing a comparative method between the classical commentary of Ath-Tabari and the contemporary commentary of al-Maraghi. The research data were obtained through a literature review of primary and secondary sources, while the analytical technique used was content analysis with a qualitative approach. The focus of the study is on how the two commentators interpret Qur’anic verses related to religious moderation and their relevance to the lives of Muslims. The  findings  indicate  that  Ath-Tabari  understands  moderation as a  normative and theological commitment to Islamic belief and law, emphasizing textual, historical, and asbab al-nuzul. Meanwhile, al-Maraghi emphasizes moderation in a social and practical dimension by highlighting tolerance, morality, and the relevance of Islamic teachings in a pluralistic modern society. These differences in interpretive approaches demonstrate that classical and contemporary perspectives complement one another, thereby providing a more comprehensive under-standing of the value of religious moderation in the Qur’an. This article contributes to enriching the body of thematic Qur’anic interpretation on religious moderation, particularly as an academic and normative reference in responding to the challenges of extremism, intolerance, and socio-religious diversity.